Arterial stiffness index, physical activity and food and nutrient intake: cross-sectional study in adults aged 40 years and older - Eun-A Kim; Yun-Mi Kim; Eun-Kyung Kim (Korean Journal of Community Nutrition, 2024)
Abstract Objectives This study aimed to investigate arterial stiffness index, physical activity, and food and nutrient intake in middle-aged adults over 40 years when the incidence of cardiovascular disease begins to increase.